2019
DOI: 10.4054/mpidr-wp-2019-007
|View full text |Cite
|
Sign up to set email alerts
|

Universal family background effects on education across and within societies

Abstract: The extent to which siblings resemble each other measures the total impact of family background in shaping life outcomes. We study sibling similarity in cognitive skills, school grades, and educational attainment in Finland, Germany, Norway, Sweden, the United Kingdom, and the United States. We also compare sibling similarity by parental education and occupation within these societies. The comparison of sibling correlations across and within societies allows us to characterize the omnibus impact of family back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In contrast to studies using intergenerational correlations of union dissolution, relatively little research exists regarding sibling correlations in union dissolution, leaving important descriptive research questions unattended. Future research may, for example, apply this approach comparatively (Grätz et al, 2019) Family 192,794 103,259 106,835 192,516 195976 99,458 102,994 186,011 Individual 218,040 107,113 110,927 200,129 209526 102,910 106,616 192,745…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to studies using intergenerational correlations of union dissolution, relatively little research exists regarding sibling correlations in union dissolution, leaving important descriptive research questions unattended. Future research may, for example, apply this approach comparatively (Grätz et al, 2019) Family 192,794 103,259 106,835 192,516 195976 99,458 102,994 186,011 Individual 218,040 107,113 110,927 200,129 209526 102,910 106,616 192,745…”
Section: Discussionmentioning
confidence: 99%
“…Finding no cross-country differences would indicate that sibling similarity stems solely from family-level mechanisms not influenced by contextual differences. Previous research has found institutional and cross-country variation in educational inequalities, although studies do not agree on the rankings of countries in this respect (e.g., Bar Haim and Shavit, 2013;Breen et al, 2010Breen et al, , 2009Grätz et al 2019;Pfeffer, 2008;Pöyliö et al, 2018; Van de Werfhorst and Mijs, 2010).…”
Section: Aimsmentioning
confidence: 96%
“…Few previous studies have addressed cross-country differences in sibling similarities in education. Some previous studies have analyzed sibling similarities in education across several countries, finding few cross-country differences (Björklund and Salvanes, 2011;Grätz et al 2019;Sieben et al, 2001;Sieben and Graaf, 2003). Results concerning temporal trends in sibling correlations in education are inconclusive.…”
Section: Sibling Correlations In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the country has been considered as a society with a high level of equality of opportunity, meaning that parental socioeconomic status determines children's adult socioeconomic outcomes relatively weakly. This has been found out to be true for various socioeconomic outcomes-including education, occupational status, and income (Björklund and Jäntti, 2000;Jäntti et al, 2006;Pfeffer, 2008;Erola, 2009;Grätz et al, 2019). The reasons for openness are subject to debate, but often cited explanations which include high-quality early childcare (Karhula et al, 2017;Hiilamo et al, 2018), high-quality and a free of charge educational system (Pekkarinen et al, 2006;OECD, 2008) and strong public support for the egalitarian welfare state (Forma, 2012).…”
Section: Institutional Contextmentioning
confidence: 99%